2008
DOI: 10.5194/nhess-8-751-2008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of directivity in seismic site response from microtremor spectral analysis

Abstract: Abstract.Recent observations have shown that slope response to seismic shaking can be characterised by directional variations of a factor of 2-3 or larger, with maxima oriented along local topography features (e.g. maximum slope direction). This phenomenon appears influenced by slope material properties and has occasionally been detected on landslide-prone slopes, where a down-slope directed amplification could enhance susceptibility to seismically-induced landsliding. The exact conditions for the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 10 publications
(15 reference statements)
5
40
0
1
Order By: Relevance
“…These new SSR results appear consistent with those obtained from the first ambient noise recording campaign carried out in July 2007 using a Tromino tomograph prototype (Del Gaudio et al, 2008). The azimuthal variation of HVNR values in Fig.…”
Section: Measurements At Accelerometer Sites On Landslide-prone Slopessupporting
confidence: 80%
See 2 more Smart Citations
“…These new SSR results appear consistent with those obtained from the first ambient noise recording campaign carried out in July 2007 using a Tromino tomograph prototype (Del Gaudio et al, 2008). The azimuthal variation of HVNR values in Fig.…”
Section: Measurements At Accelerometer Sites On Landslide-prone Slopessupporting
confidence: 80%
“…The presence of H /V peaks at site resonance frequencies is explained by assuming that horizontal and vertical components of noise wave field have a comparable amplitude at the substratum (within an approximation factor of 2) and that only horizontal components are significantly amplified by the effect of shallow layers. Some preliminary tests on landslide areas showed that an analysis of azimuthal variation of H /V spectral ratios can reveal the occurrence and orientation of directional resonance possibly related to sliding directions (Del Gaudio et al, 2008).…”
Section: Del Gaudio Et Al: New Developments In Ambient Noise Analmentioning
confidence: 99%
See 1 more Smart Citation
“…The source magnitude controls the area affected by landslides [1] relating the ground motion decay with distance to the epicenter or to the fault plane (e.g., [3]). However this generic law is affected by different factors: (1) a significant over-abundance of landslides in the hanging walls of ruptured thrust faults relative to the footwalls rate are reported (e.g., [4,5]), showing the effect of the dynamics of the fault rupture on the landslide distribution; (2) the greater erosion rate due to precipitations observed after the earthquake [8,10] shows that earthquakes are found to interact non-linearly with precipitations; (3) the site effect, or amplification of the seismic waves due to shear-wave velocity contrast between the landslide material and the stable material [11,12] or topographical particularities like ridges [9]. This topographic control on co-seismic landslides has also been pointed out through different parameters: convexity [7], slopes, proximity from ridges and crests [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recordings of ambient noise and the use of the HVSR technique have recently had widespread use in studying landslides (e.g. Del Gaudio et al, 2008;Burjánek et al, 2010;Del Gaudio and Wasowski 2011;Burjánek et al, 2012).…”
Section: Introductionmentioning
confidence: 99%